(untitled) (Global Journal of Human-Social Science, 2015)
Energy is inevitable for development and its demand is increasing day by day. Energy is essential and important for human life. However, energy from fossil fuel (coals, diesel, kerosene, wood etc.) generates carbon, carbon dioxide emissions, green house emissions that pollute air, and destroy environment resulted global warming that’s harmful to living beings and nature. Hence energy scientists are looking for alternative energy resources uses that are environmentally friendly and good for human being. They are provoking for renewable energy (solar radiation energy, bio gas energy, wind energy, water wave energy, CNG energy and hydropower energy) use because PV technologies produce very small amount of CO2 compared to the emissions from conventional existing fossil fuel energy technologies. Therefore, renewable energy (RE) uses is less harmful to living beings and environment (air, water and land). This paper talks about fossil fuel energy and renewable energy use and their consequence and impact respectively in the nature and society.